The effect of peer-led education on the quality of life of mothers of premature infants in neonatal intensive care units: a quasi-experimental study - Jamalodin Begjani; Fatemeh Khoshnavay Fomani; Farzane Beiranvand; Mohammad Mehdi Rajabi (BMC Research Notes)
Abstract Objective The hospitalization of a premature infant in a neonatal intensive care unit (NICU) is a stressful experience for mothers, often reducing their quality of life (QoL). This study evaluated the effect of a peer-led educational and supportive program on the QoL of mothers with premature infants. A quasi-experimental study was conducted in the NICUs of Hazrat Vali-e-Asr Hospital, Tehran, Iran. Seventy mothers were enrolled and non-randomly assigned to an intervention group (n = 35) or a control group (n = 35) based on the ward where their infant was hospitalized. The intervention group attended three peer-led sessions over ten days. The control group received standard NICU education from nurses. QoL was measured using the Short Form Health Survey (SF-36) at baseline and one month after the intervention. Data were analyzed using independent t-tests and ANCOVA. Results At baseline, there was no significant difference in QoL scores between groups (P = 0.89). Post-intervention, the intervention group showed significantly higher total QoL scores than the control group (P < 0.001). Significant improvements were noted in mental health, vitality, social functioning, and role limitations due to emotional problems (all P < 0.001). These findings suggest peer-led programs can improve maternal QoL in NICUs and support their integration into neonatal care. Trial registration This study was retrospectively registered in the Iranian Registry of Clinical Trials on July 20, 2025 (IRCT20230816059164N4; https://irct.behdasht.gov.ir/trial/84566 ).